2011
DOI: 10.1590/s1679-87592011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Fouling assemblages associated with estuarine artificial reefs in new South Wales, Australia

Abstract: Previous studies examining the dynamics of succession on artificial reefs have predominantly focussed on fish communities and largely ignored the role of fouling assemblages in explaining the patterns of community structure associated with artificial reefs. The objective of this study was to record the development of epibiotic assemblages on three "design specific" (Reef Ball ®) estuarine artificial reefs systems located in Lake Macquarie, Botany Bay and St Georges Basin in New South Wales, Australia. Recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The artificial reefs were constructed as part of a larger study to investigate the use of artificial reef in three coastal estuaries along Australia's south east coast in the State of New South Wales [21][24]. Lake Macquarie (33°09' S 151°66' E), Botany Bay (33°00' S 151°23' E) and St Georges Basin (35°18' S 150°59 E) have a total area of 114 km2, 38 km2 and 42 km2 respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial reefs were constructed as part of a larger study to investigate the use of artificial reef in three coastal estuaries along Australia's south east coast in the State of New South Wales [21][24]. Lake Macquarie (33°09' S 151°66' E), Botany Bay (33°00' S 151°23' E) and St Georges Basin (35°18' S 150°59 E) have a total area of 114 km2, 38 km2 and 42 km2 respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The combined summer/autumn season (approximately 6 months in each estuary) provided a comparable time period, limiting temporal bias associated with seasonal variation. It should be noted that the time period was selected as it was the oldest comparable data available, representing an artificial reef age of >1 year; which based on fish and benthic assemblage development studies of the artificial reefs [22], [24], represented an assemblage that had progressed through the initial rapid development stage and was approaching early stages of assemblage stability.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to other assemblage parameters, diversity was found to be similar between human-made rock walls and natural reefs in both studies that investigated it (Fowler and Booth 2013;Porter et al 2018). Only two papers have studied the fouling assemblages on artificial habitats in Gamay (Knott et al 2004;Mckenzie et al 2011), which is a small number compared with the neighbouring estuary, Sydney Harbour, which has >20 studies on artificial habitats. Knott et al (2004) found that many fouling invertebrate taxa showed clear differences regarding their cover between natural rocky reefs and concrete breakwalls in Gamay.…”
Section: Artificial Substratesmentioning
confidence: 90%
“…This contrasts with Lake Macquarie where reef ball-associated fish biomass is more evenly distributed among plankton, macrophytes and detritus. Epibenthic assemblages have been assessed on Mini Bay Reef Balls in Gamay, with a total of 16 taxa found, higher than on reef balls deployed in both Lake Macquarie and Georges Basin (Mckenzie et al 2011).…”
Section: Artificial Substratesmentioning
confidence: 99%